(untitled) (Asian-Australasian Journal of Bioscience and Biotechnology, 2016)
To determine the effect of milking hygiene on keeping quality of milk at room temperature, 15 “Red Chittagong” milking cows were randomly and equally distributed under three different milking hygiene conditions (just previous to milking) such as T1=Washing and disinfection of udder and teats, milkers’ hands, and a sanitary rinse of milking pails with home-made calcium hypochlorite solution (200ppm Cl); T2=Washing of udder and teats, milkers’ hands, and milking pails with normal farm water; and T3=dry milking without any preparation of cows’ udder and teats , milkers’ hands and milking pails. Microbial study revealed an average Standard Plate Count (million cfu/ml) respectively for T1, T2, and T3 of 0.057±0.014, 0.708±0.8 and 0.161±0.037 at 0 hr; 0.263±0.080, 2.548±0.780 and 0.746±0.170 at 4 hr; 1.820±0.370, 18.711±5.050 and 5.578±1.840 at 8 hr; and 20.478±4.050, 25.578 ±2.200 and 22.367±3.400 at COB+ve. Average coliform count (thousand cfu/ml) were 0.038±0.024, 0.359±0.092 and 0.123±0.022 at 0 hr; 0.166 ± 0.100, 1.754±0.450 and 0.510±0.110 at 4 hr; 0.990±0.500, 12.810±4.010 and 3.350±0.850 at 8 hr; and 20.456±8.610, 25±5.440 and 24.440±5.460 at COB+ve respectively for T1, T2, and T3. Microbial counts up to 8hr were significantly (p<0.01) different among treatments. The methylene Blue Reduction Time were significantly (p<0.01) different at different holding and a reduction time of 5.5 hr or more (>330 min.) was retained for at least 6 hr by milk of T1, for only 2 hr by T2 milk and for 4 hr by T3 milk. There were non-significant differences in MBRT at COB+ve. Average acidity percentage were 0.1584, 0.1622 and 0.1611 at 0 hr; 0.1667, 0.1778 and 0.1683 at 4 hr; 0.1800, 0.2103, and 0.1846 at 8 hr; and 0.240, 0.258 and 0.240 at COB+ve respectively for T1, T2 and T3. There were no significant differences in acidity percentage initially and at COB+ve. Average COB+ve time were 12.39, 8.83 and 11.94 hr, and normal smell of milk retained on an average up to10.83 , 6.22 and 8.83 hr, respectively for T1, T2 and T3. Both the COB+ve time and normal smell hr of T1 milk were significantly higher (p<0.01). Keeping quality time calculated by averaging the results of COB+ve time and evaluation of milk smell (hr) were on an average 11.67hr, 8hr and 10.08 hr respectively for T1, T2 and T3. Milk produced with better milking hygiene showed longer keeping quality time. Asian Australas. J. Biosci. Biotechnol. 2016, 1 (2), 199-205